Performance improvement of profiled steel sheet dry board floor system by concrete infill - Badaruzzaman W.H.W.; Shodiq H.M.; Eng J. (School of Engineering and Technology, 2023)
The Profiled Steel Sheeting Dry Board (PSSDB) system is a type of lightweight composite structural system constructed from profiled steel sheeting and dry board connected by selfdrilling and self-tapping screws. The PSSDB system can be applied as flooring, walling and roofing panels in buildings. This paper focuses on studying the enhancement of the structural performance of the PSDDB floor system with the introduction of concrete infill in the trough of the profiled steel sheet. The study was conducted through theoretical and experimental approach. The finite element and simple beam models developed have been shown able to predict the behavior of the PSSDB floor system with concrete infill with a very high level of accuracy, i.e. in between 5% to 10%. It has been proven theoretically and experimentally that concrete as an infill material can increase the performance of the floor system compared to the original system without any infill material. Results found that with the use of concrete infill, the deflection at mid-span of the PSSDB floor system has been reduced up to 19%. This indicated an enhancement in the stiffness of the system. 2006 by School of Engineering and Technology, Asian Institute of Technology.